Automated current control for pulse anodic etching of porous silicon - Ahmad Bukhairi Md. Rashid, 1994- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2017